2010
DOI: 10.1104/pp.110.162057
|View full text |Cite
|
Sign up to set email alerts
|

Light Quality-Mediated Petiole Elongation in Arabidopsis during Shade Avoidance Involves Cell Wall Modification by Xyloglucan Endotransglucosylase/Hydrolases      

Abstract: Some plants can avoid shaded conditions via rapid shoot elongation, thus growing into better lit areas in a canopy. Cell wallmodifying mechanisms promoting this elongation response, therefore, are important regulatory points during shade avoidance. Two major cell wall-modifying protein families are expansins and xyloglucan endotransglucosylase/hydrolases (XTHs). The role of these proteins during shade avoidance was studied in Arabidopsis (Arabidopsis thaliana). In response to two shade cues, low red to far-red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
156
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(166 citation statements)
references
References 63 publications
7
156
1
2
Order By: Relevance
“…Direct PIF regulation of cell wall metabolism, possibly related to the rapid growth responses to shade, is also suggested by the presence of XTR7/XTH15 (a xyloglucan transglycosylaseencoding gene; Rose et al, 2002) in this group. This is consistent with the observation that xth15 knockout mutants show reduced shade-induced growth responses (Sasidharan et al, 2010). Collectively, the data focus attention on a subset of genes that provide potential targets for future investigations aimed at securing more detailed insight into central cellular processes involved in the initiation of the shade avoidance response.…”
Section: It Is Notable That Bhlh Factor Genes (Pil1 Hfr1 Par1 Bes1supporting
confidence: 72%
“…Direct PIF regulation of cell wall metabolism, possibly related to the rapid growth responses to shade, is also suggested by the presence of XTR7/XTH15 (a xyloglucan transglycosylaseencoding gene; Rose et al, 2002) in this group. This is consistent with the observation that xth15 knockout mutants show reduced shade-induced growth responses (Sasidharan et al, 2010). Collectively, the data focus attention on a subset of genes that provide potential targets for future investigations aimed at securing more detailed insight into central cellular processes involved in the initiation of the shade avoidance response.…”
Section: It Is Notable That Bhlh Factor Genes (Pil1 Hfr1 Par1 Bes1supporting
confidence: 72%
“…Interestingly, microarray analysis on petioles from canopy plants at LAI 1.0 showed no induced expression of genes known to be involved in shade avoidance (Dataset 1 and Table S1). Accordingly, a quantitative RT-PCR time course throughout canopy development indicated that expression of the low R:FR-inducible marker genes ATHB2 and XTH15 (15,16) was not induced at the onset of hyponasty (LAI 0.65). These genes were only up-regulated after petiole elongation occurred in canopy plants at an LAI >1.27, which corresponded with a R:FR <1.3 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the expression of XTH (XYLOGLUCAN ENDOTRANSGLUCOSYLASE/HYDROLASE) genes regulated by PIFs and/or IAA and/or BL has been linked to growth promotion (Hornitschek et al, 2009;Sasidharan et al, 2010;Keuskamp et al, 2011;de Wit et al, 2015;Pedmale et al, 2016). Our organ-specific analysis allowed us to test whether shade-induced expression of XTH genes selectively occurred in the fast growing hypocotyl.…”
Section: Shade Treatment Leads To a Strong Genomic Signature Of Enhanmentioning
confidence: 99%